College Students' Knowledge about Meningococcal Disease and Preferences for Health Information - Sharon Bernecki DeJoy; Karen M (Kay); Shenghua Zha; Somer Goad Burke (University of North Florida, 2008)
The purpose of this study was to measure college students' knowledge about meningococcal disease, preferred sources of health information, and vaccine intentions. Participants included 519 students taking online undergraduate courses in public health. We developed and administered a brief, ten-question online survey, which was posted on BlackBoard®. Students demonstrated a high level of knowledge about risk factors for meningococcal disease, but reported a need for more information, preferably delivered through electronic media. About a third of students had received the meningococcal vaccine prior to the survey; students who lived on campus were more likely to be vaccinated. Further research is needed to determine the best methods of preventing meningococcal disease among college students.